The good women of the parish : gender and religion after the Black Death - French, Katherine L. (University of Pennsylvania Press, 2008)
French argues that medieval laywomen both coped with the chaotic changes following the plague and justified their own changing behavior by participating in local religion. Through active engagement in the parish church, the basic unit of public worship, women promoted and validated their own interests and responsibilities.
Keywords: Parishes -- England -- History -- To 1500.; Parishes -- England -- History -- 16th century.; Women -- Religious life -- England -- History -- To 1500.; Women -- Religious life -- England -- History -- 16th century.; Women in church work -- England -- History -- To 1500.; Women in church work -- England -- History -- 16th century.; Women -- England -- Social conditions -- 16th century.; Women -- England -- History -- Middle Ages, 500-1500.; Black Death -- Social aspects -- England.; Paroisses -- Angleterre -- Histoire -- 16e siècle.; Femmes -- Vie religieuse -- Angleterre -- Histoire -- 16e siècle.; Femmes -- Angleterre -- Conditions sociales -- 16e siècle.; Femmes -- Angleterre -- Histoire -- 500-1500 (Moyen Âge); Peste noire -- Aspect social -- Angleterre.; HISTORY -- Medieval.; Black death -- Social aspects; Parishes; Women in church work; Women -- Middle Ages; Women -- Religious life; Women -- Social conditions; England; To 1599; History